Characterizing advanced Parkinson’s disease: OBSERVE-PD observational study results of 2615 patients - Alfonso Fasano; Victor S.C. Fung; Leonardo Lopiano; Bülent Elibol; И. Г. Смоленцева; Klaus Seppi; Annamária Takáts; Koray Onuk; Juan Carlos Parra; Lars Bergmann; Kavita Sail; Yash J. Jalundhwala; et al. (2019)
There are currently no standard diagnostic criteria for characterizing advanced Parkinson's disease (APD) in clinical practice, a critical component in determining ongoing clinical care and therapeutic strategies, including transitioning to device-aided treatment. The goal of this analysis was to determine the proportion of APD vs. non-advanced PD (non-APD) patients attending specialist PD clinics and to demonstrate the clinical burden of APD. OBSERVE-PD, a cross-sectional, international, observational study, was conducted with 2615 PD patients at 128 movement disorder centers in 18 countries. Motor and non-motor symptoms, activities of daily living, and quality-of-life end points were assessed. The correlation between physician's global assessment of advanced PD and the advanced PD criteria from a consensus of an international group of experts (Delphi criteria for APD) were evaluated. According to physician's judgment, 51% of patients were considered to have APD. There was a moderate correlation between physician's judgment and Delphi criteria for APD (K = 0.430; 95% CI 0.406–0.473). Activities of daily living, motor symptom severity, dyskinesia duration/disability, "Off" time duration, non-motor symptoms, and quality-of-life scores were worse among APD vs. non-APD patients (p < 0.0001 for all). APD patients (assessed by physicians) had higher disease burden by motor and non-motor symptoms compared with non-APD patients and a negative impact on activities of daily living and quality of life. These findings aid in identifying standard APD classification parameters for use in practicing physicians. Improvements in identification of APD patients may be particularly relevant for optimizing treatment strategies including transitioning to device-aided treatment.